Clinical and diagnostic aspects of deep infiltrative endometriosis (diagnosis, treatment, recurrence) - Shakhnoza K. Muftaidinova; Leonid Z. Faizullin; Vladimir D. Chuprynin; Nikolai S. Ruseikin; Tatiana I. Smolnova; Natalia A. Buralkina (IP Berlin A.V., 2021)
Aim. To analyze the recurrence of endometriosis after surgical treatment of patients with deep endometriosis. Materials and methods. The case histories of 90 patients aged 19 to 45 years were retrospectively analyzed. The study group consisted of 70 endometriosis patients: 20 with peritoneal endometriosis and 50 with deep infiltrative endometriosis (DIЕ). The comparison group included 20 women without endometriosis. There was an in-depth study of anamnestic data in the cohort of patients under study. The results of preoperative laboratory tests, including serum levels of the CA-125 and CA 19-9 oncomarkers, were processed. Results. Analysis of the obtained data showed that about half of the DIE patients (54%) in the main group had a history of surgical interventions for endometriosis. The number of operations was significantly higher in patients compared to the peritoneal endometriosis group (68% vs 20%, respectively; р=0.0012). Two subgroups were formed from the group of women with DIE: patients who had no history of previous surgical treatment for endometriosis and those hospitalized for repeated surgical treatment of endometriosis (patients with recurrent endometriosis). Patients with recurrent endometriosis had a significantly higher incidence of heavy menstruation, pregnancy terminations (abortions), and a high proportion of gastrointestinal diseases. Analysis of the hormonal therapy received in patients with DIE showed that every second patient with relapses (18/53%) after surgical treatment and every third patient without a prior history of surgery (5/31%) received hormonal therapy. Examination of the preoperative serum levels of CA-125 and CA 19-9 serum markers in patients with DIE showed an increase in their serum levels and a correlation with the frequency of endometriosis recurrence and the size of DIE foci. Conclusion. Despite the conservative and surgical treatment of DIE patients, the recurrence rate is still high. At present, there is no satisfactory therapy for all endometriosis patients. Therefore, the development of therapy for the conservative treatment of the disease remains an urgent task.